Electrical conductivity of the thermal dusty plasma under the conditions of a hybrid plasma environment simulation facility. (May 2015) - Zhukhovitskii, Dmitry I; Petrov, Oleg F; Hyde, Truell W; Herdrich, Georg; Laufer, Rene; Dropmann, Michael; Matthews, Lorin S
Abstract We discuss the inductively heated plasma generator (IPG) facility in application to the generation of the thermal dusty plasma formed by the positively charged dust particles and the electrons emitted by them. We develop a theoretical model for the calculation of plasma electrical conductivity under typical conditions of the IPG. We show that the electrical conductivity of dusty plasma is defined by collisions with the neutral gas molecules and by the electron number density. The latter is calculated in the approximations of an ideal and strongly coupled particle system and in the regime of weak and strong screening of the particle charge. The maximum attainable electron number density and corresponding maximum plasma electrical conductivity prove to be independent of the particle emissivity. Analysis of available experiments is performed, in particular, of our recent experiment with plasma formed by the combustion products of a propane–air mixture and the CeO2 particles injected into it. A good correlation between the theory and experimental data points to the adequacy of our approach. Our main conclusion is that a level of the electrical conductivity due to the thermal ionization of the dust particles is sufficiently high to compete with that of the potassium-doped plasmas.